Technical project of a digital platform for social monitoring of water bodies - Beresneva Yana; Krasnikova Irina (E3S Web of Conferences)
The article presents a project for creating a specialized software product designed to collect, process, and store data on the condition of water bodies. A distinctive feature of the project is the involvement of citizens in data collection, even if their professional duties are unrelated to environmental issues or other processes specific to the water sector. By applying methods of system analysis, data modeling, and object-oriented design, the functionality of the software product was developed, its architectural structure established, and both a data model and user interface layout created. Implementing the project enables the use of smart monitoring technology through integrating artificial intelligence for processing heterogeneous data. The developed functional capabilities facilitate the operational management of water bodies' conditions, positively influencing the socio-economic development of the region and improving the ecological state of ecosystems.